Improving Hypoxia Adaption Causes Distinct Effects on Growth and Bioactive Compounds Synthesis in an Entomopathogenic Fungus Cordyceps militaris - Wang, Ying; Yang, Zhanshan; Bao, Dapeng; Li, Bo; Yin, Xin; Wu, Yingying; Chen, Hongyu; Tang, Guirong; Li, Nanyi; Zou, Gen (Frontiers in Microbiology, 2021)
Cordyceps militaris is an entomopathogenic fungus producing a variety of bioactive compounds. To meet the huge demand for medicinal and edible products, industrialized fermentation of mycelia and cultivation of stromata have been widely developed in China. The content of bioactive metabolites of C. militaris, such as cordycepin, is higher when cultivated on silkworm pupae than on rice or in broth. However, compared with other cultivation methods, C. militaris grows more slowly and accumulates less biomass. The hypoxic environment in pupa hemocoel is one ofa unique environmental factor which is not existed in other cultivation methods. It is suggested that hypoxia plays an important role on the growth and the synthesis of bioactive compounds in C. militaris. Here, we demonstrated that the distinct effects on the growth and synthesis of bioactive compounds employing different strategies of improving hypoxia adaption. Through the introduction of Vitreoscilla hemoglobin enhanced growth, biomass accumulation, and crude polysaccharides content of C. militaris were enhanced. However, cordycepin production was decreased to 9%–15% of the control group. Meanwhile, the yield of adenosine was increased significantly accumulated because it could not be converted into cordycepin. Nonetheless, when the predicted bHLH transcription factor of sterol regulatory element binding proteins (SREBPs) was overexpressed in C. militaris to improve the hypoxia adaption of fungal cells, cordycepin content was significantly increased more than 2-fold. However, the self-toxicity of cordycepin probably caused the reduced accumulation of mycelial biomass. These findings reveal the role of SREBPs on growth and bioactive compounds synthesis. And it also provides a scientific basis for rationally engineering strains and optimization strategies of air supply in cultivation and fermentation.